Scaffold Development Using Biomaterials: A Review. (2018) - Deb, Payel; Deoghare, Ashish B.; Borah, Animesh; Barua, Emon; Das Lala, Sumit
Abstract: The main objective of tissue engineering (TE) is to develop biological substitutes that maintain, improve or restore tissue functions. Scaffolds are of great significance for TE because they are capable of providing a healthy environment for cells attachment, differentiation, proliferation and migration during both in vitro culture and in vivo implantation. Research has been gradually inclining towards the biological integration of implant materials with the host tissue. The mechanical and physiological characteristics of the biomaterials used for scaffolding are expected to be similar to the native tissues. Hence, Biomaterial selection and fabrication techniques are playing a significant role in the preparation of scaffold in TE. This review article is intended to illustrate a summary of state-of-the-art biomaterials and synthesis techniques for scaffold development for specific biomedical environment.